School and Family Support for Social-Emotional Competence Among Higher Vocational Students the Mediating Role of Basic Psychological Need Satisfaction - Hu, Xinghong; Wang, Feifei; Senarith, Prapatpong (Rajapark Journal, 2026)
This study aimed to examine: (1) the direct relationships of school climate and parental autonomy support with social-emotional competence among higher vocational students in Chongqing, China; (2) the mediating role of autonomy satisfaction, relatedness satisfaction, and competence satisfaction in these relationships; and (3) the fit of an integrated structural model linking school climate, parental autonomy support, basic psychological need satisfaction, and social-emotional competence. Grounded in ecological systems theory, self-determination theory, and stage-environment fit theory, the study used cluster sampling to collect questionnaire data from 656 higher vocational students. Structural equation modeling and bootstrap analysis were used to test the proposed model. The results showed, first, that both school climate and parental autonomy support significantly and positively predicted social-emotional competence. Second, both school climate and parental autonomy support significantly and positively predicted satisfaction with autonomy, relatedness, and competence, and the three need-satisfaction dimensions each significantly predicted social-emotional competence. Bootstrap results further confirmed that all six indirect paths were significant, indicating that autonomy satisfaction, relatedness satisfaction, and competence satisfaction functioned as parallel partial mediators. Third, the integrated model demonstrated satisfactory fit, with CMIN/DF = 1.056, CFI = 0.992, TLI = 0.992, SRMR = 0.066, and RMSEA = 0.009. These findings suggest that supportive school and family contexts are important external resources for higher vocational students’ social-emotional competence, and that basic psychological need satisfaction is a key psychological mechanism linking contextual support to competence development.